“You can't shoot another bullet until you've reloaded the gun”: Coaches' perceptions, practices and experiences of deloading in strength and physique sports - Bell, Lee; Nolan, David; Immonen, Velu; Helms, Eric; Dallamore, Jake; Wolf, Milo; Androulakis Korakakis, Patroklos (Frontiers in Sports and Active Living, 2022)
Deloading refers to a purposeful reduction in training demand with the intention of enhancing preparedness for successive training cycles. Whilst deloading is a common training practice in strength and physique sports, little is known about how the necessary reduction in training demand should be accomplished. Therefore, the purpose of this research was to determine current deloading practices in competitive strength and physique sports. Eighteen strength and physique coaches from a range of sports (weightlifting, powerlifting, and bodybuilding) participated in semi-structured interviews to discuss their experiences of deloading. The mean duration of coaching experience at ≥ national standard was 10.9 (SD = 3.9) years. Qualitative content analysis identified Three categories: definitions, rationale, and application. Participants conceptualised deloading as a periodic, intentional cycle of reduced training demand designed to facilitate fatigue management, improve recovery, and assist in overall training progression and readiness. There was no single method of deloading; instead, a reduction in training volume (achieved through a reduction in repetitions per set and number of sets per training session) and intensity of effort (increased proximity to failure and/or reduction in relative load) were the most adapted training variables, along with alterations in exercise selection and configuration. Deloading was typically prescribed for a duration of 5 to 7 days and programmed every 4 to 6 weeks, although periodicity was highly variable. Additional findings highlight the underrepresentation of deloading in the published literature, including a lack of a clear operational definition.